INFLUENCE OF SOCIAL COGNITION AND SELF EFFICACY ON PROBLEM SOLVING ABILITY OF SERVICE STUDENTS AT STID MOHAMMAD NATSIR - Giyanti, Ummu Ahya; Ahmad Misbahul Anam (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2023)
The purpose of this study to know how the influence of social cognition on problem-solving ability of service students at STID Mohammad Natsir; how the influence of self-efficacy of problem-solving ability in service students at STID Mohammad Natsir; and how the influence of social cognition and self-efficacy simultaneously on problem-solving ability of service students at STID Mohammad Natsir. This research used descriptive quantitative with survey design. The population and sample in this study are students of STID Mohammad Natsir who have served for two years in various regions in Indonesia. Data collection in this study using questionnaires. Analysis of validity test used the Pearson product moment while reliability test used Cronbach’s Alpha. Technique of data analysis used classical assumption tests (normality, linearity, multicollinearity) and multiple regression analysis (heteroscedasticity tests, partial hypothesis tests, simultaneous hypothesis tests, coefficient determination tests). The results of this study showed that social cognition had a significant influence on students' problem-solving abilities with a comparative score of t-count > t-table, 3.214 > 1.999, while the significance value was 0.02 < 0.05. The second finding, self-efficacy had a significant influence on students' problem-solving abilities with a comparative score of t-count > t-table, 4.343 > 1.999 with a significance value of 0.00 < 0.05. Further findings, simultaneously between the variables of social cognition and self-efficacy exerted a significant influence on problem-solving ability. It is showed by a calculated F-value greater than the F-table, score ratio is 42.469 > 3.15. Judging from the significance score 0.00 < 0.05 indicated social cognition and self-efficacy affect problem-solving ability. From the test results of the coefficient of determination with score of R-squared 0.578. So, it shows that social cognition and self-efficacy contribute simultaneously to problem-solving ability reaching 57.8%. The remaining 42.2% indicated a contribution from other variables that were not used in this study.